Earthquake Disaster Risk Reduction Based on Islamic Religious Education Curriculum in Indonesia - Muzani Muzani (International Journal of Education, Information Technology, and Others, 2020)
This paper discusses earthquake risk reduction based on Islamic religious education curriculum. Indonesia is an archipelago located at the confluence of tectonic plates. This causes frequent earthquakes. In an effort to reduce the risks caused by the earthquake the Government, through the Minister of National Education since 2010 has given serious attention to the issue of disasters. One of them is through the integration of disaster lessons into the school curriculum. This paper analyzes the Disaster Risk Reduction based on Islamic Religious Education Curriculum. The result is that fiqh, creed, morals, al-quran and Hadith are very worthy to be integrated with disaster lessons.